Rescue Thrombectomy for Early Hepatic Artery Thrombosis Using Stent Retriever in a Child Post Combined Deceased Donor Liver and Renal Transplant - Yadav, Manish Kumar; Unni, Madhavan; Ali, Shabeer, U.T.; Rather, Shiraz Ahmed; Venugopal, B. (Journal of Clinical Interventional Radiology ISVIR, 2021)
We report this case of a 5-year-old child post combined liver and renal transplant for primary hyperoxaluria. Patient developed hepatic artery thrombosis on day 3 posttransplant that was managed by reexploration and reanastomosis of the hepatic artery. On day 4, the patient again developed hepatic artery thrombosis that failed to revascularize by surgical exploration and reanastomosis. Tissue plasminogen activator was injected into the hepatic artery intraoperatively to lyse any clot; however, no revascularization could be achieved. Subsequently, catheter angiogram confirmed no flow in the hepatic artery. A4 × 22 mm revive stent retriever was deployed across the site of occlusion and retrieved after 5 minutes of indwell time. Two such passes were made and complete recanalization of the hepatic artery was achieved. The hepatic artery remained patent as confirmed on serial Doppler images post intervention.
Keywords: combined deceased donor liver and renal transplant; hepatic artery thrombosis; stent retriever; mechanical thrombectomy